Confederaciones interprovinciales y grandes señores interétnicos en el Tawantinsuyu - Pärssinen, Martti (Pontificia Universidad Católica del Perú, 2012)
Interprovincial Confederations and Great Inter-Ethnic Lords in TawantinsuyuThe four suyus of Tawantinsuyu were divided into various administrative provinces called guamaníes. However, there were also some interprovincial confederations as well as other inter-ethnic formations within the Inca State (e.g. Colesuyu, Collao, Charcas, etc.). They remain a much-neglected area of investigation, but we do know that some of the lords of these confederations were regarded as apocuna, "kings, captain generals and segundas personas of the Inca". For example, according to an unpublished manuscript, kept in the General Indian Archive of Seville, the grandson of the curaca of Lurin Huanca said in 1561 that his grandfather was married to an Inca daughter, and as an Inca’s son-in-law, he governed a territory up to the Quito, as he was also the lord of the parcialidades of "hananguanca, luringuanca y Jauja". While we need not take this statement too literally, we should not reject it, either, among many other independent and quite similar pieces of evidence. It seems that special privileges with interprovincial powers were indeed granted by the Incas (within the respective suyus), and especially to chiefs who distinguished themselves in military campaigns. Furthermore, some Incas related to a religious cult, such as Apu Chalco Yupanqui, the son of the first Copacabana Governor, also had great interprovincial authority, similar to that described by Sarmiento in connection with suyoyoc apo. In this article we aim to elaborate on the hypothesis that the origin of these kinds of confederations and inter-ethnic powers may have been political or religious. Additionally, it seems that religion and military powers were frequently inseparable, because every military group had its own huaca or powerful idol, commonly shared with various local ethnic groups of the same area. In general, it was the chiefs of the most important military groups that received special privileges, and it was these same groups that were later used to setting up units of political and economic administration.